APLIKASI MATEMATIKA NUMERIK UNTUK MENGHITUNG INTERNAL RATE OF RETURN DAN YIELD TO MATURITY OBLIGASI - Yudha Herlambang (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
This paper will present the application of numerical mathematic and discuss the alternative method to calculate and solve the problem about the value of Internal Rate Return  (IRR) and desired returned rate by obligation investor. As we know there are several methods to solve the calculation about IRR ,such as Interpolation Method by using the financial table and  Trial and Error Method by using IRR Function in Excel Software; but the most popular is Newton Raphson Method. In this method, the numerical case must be transferred into the NPV equation or obligation equation, and be created to  the polynomial equation in term of f(x) until the error is minimum. This method gives the same result if it is compared with several methods mentioned above for the same case. There is only approximation of 4 digits in decimals for the result. By using this method, there are still any differences of calculation result, but it’s not significant. This numerical approach can be implemented to solve the value of desired interest rate from the obligation by using the same calculation step and algorithm.